2013
DOI: 10.1007/s00701-013-1902-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of the Cloward procedure for single-level cervical degenerative spondylosis. Clinical and radiological assessment after a 22-year mean follow-up

Abstract: The Cloward technique provided excellent long-term clinical outcome in the treatment of single-level cervical degenerative spondylosis. There were no major alterations of the cervical sagittal balance, and the development of adjacent segment disease (ASD) was not specifically associated with the previous surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Positive values higher than 5° were considered to be indicative of cervical lordosis. Negative values less than 5° indi- cated cervical kyphosis (Noriega et al 2013). The results of this study showed that the orthopedic pillow significantly increased the cervical lordosis repeating results when compared to the baseline cervical lordosis measured with the neck in a neutral position while standing.…”
Section: Discussionsupporting
confidence: 48%
“…Positive values higher than 5° were considered to be indicative of cervical lordosis. Negative values less than 5° indi- cated cervical kyphosis (Noriega et al 2013). The results of this study showed that the orthopedic pillow significantly increased the cervical lordosis repeating results when compared to the baseline cervical lordosis measured with the neck in a neutral position while standing.…”
Section: Discussionsupporting
confidence: 48%
“…Only a few studies have reported outcomes of 10 years or more after ACDF surgery (12,13). These studies show improvements in pain and reduced disability ratings at long-term follow-ups compared to preoperative ratings, and recovery rates of 80% as evaluated by surgeons (12,13).…”
Section: Outcomes Of Acdf Surgerymentioning
confidence: 99%
“…Two previous studies on pain and global outcome after ACDF with a more than 10-year follow-up were found (12,13). These studies by Noriega et al (13) and Faldini et al (12) were both evaluations of the Cloward procedure and were at least partially retrospective follow-ups.…”
Section: Follow-up Over Timementioning
confidence: 99%
See 2 more Smart Citations